How Technologies like AI Affect the Profit Rate: Empirical Study for 6 Capitalist Countries - Park, Seong Jin (International Conference on ICT Convergence, 2023)
Technologies like AI contribute to automate the production of goods and services by substituting for human labor. Capitalists invest in developing technologies in order to obtain more profit and larger profit rate. However, the profit rate has gradually fallen in many countries during the last several decades. Through the empirical study for 6 countries during 1950-2019, this paper shows that the main reason for the falling rate of profit is the technological progress.
Keywords: Empirical studies; Falling-rate; Good and services; Human labor; Profit rate; Technological progress; AI; profit rate; technological progress